Excess winter cardiovascular morbidity in Ivanovo Region in 2009-2013 years - A. V. Kontsevaya; J. A. Balanova; M. M. Loukianov; M. B. Khudyakov; O. A. Belova; S. V. Romanchuk (Столичная издательская компания, 2015)
Chronic non-infectious diseases are characterized by irregular morbidity and mortality throughout a year. Aim. To study excess cardiovascular morbidity during winter in Ivanovo Region in 2009-2013 years. Material and methods. Excess winter morbidity index (EWMI) was calculated using special formula. The incidence of cardiovascular diseases (CVDs) was determined according to the data from the medical information-analytic center of Ivanovo Region. The index was calculated for CVDs in general, for arterial hypertension (HT) and for acute forms of CVDs (acute myocardial infarction and stroke). Results. The mean EWMI for CVDs for 5 years of the follow-up made up to 77.2% and was higher in women than in men (80% vs 69.5%, respectively). People of working age had lower excess winter morbidity than the population older than working age (53.1% and 88%, respectively). EWMI for CVDs had significant variability and ranged from 29.0% (2013 year) to 81.1% (2010 year) in men and from 25.2% to 82.9% in women in the same years. In general, the 5-year mean EWMI for HT was 72.7%; it was higher in men than in women in most of the analyzed years of follow-up. We had revealed the heterogeneity of the EWMI for HT during the analyzed period in each analyzed group (the minimal values were found in 2011 after the heat wave in 2010). EWMI for myocardial infarction demonstrated excess winter morbidity, men and women had in general similar indices (31.0% and 28.4%, respectively), but it was higher in people of working age as compared with the older ones. This index had a wide range of values. In case of stroke we had revealed no excess winter morbidity; this index was equal throughout a year. Conclusion. The influence on excess winter morbidity can result in the reduction of cardiovascular morbidity and mortality due to the decreased effect of risk factors; it would also optimize a load on healthcare system, the season irregularity of which must be taken into account when planning a work of medical centers.